IN VITRO ANTIOXIDANT AND CYTOTOXIC PROPERTIES OF FUCOIDAN FROM THREE INDIAN BROWN SEAWEEDS - SREEKALA KANNIKULATHEL GOPIDAS; NAGARAJ SUBRAMANI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: In the present study, fucoidan extracted from three brown algae, Sargassum wightii, Turbinaria ornata, and Padina tetrastromatica, was purified, characterized, and evaluated for antioxidant and cytotoxic properties. Methods: Algal powders were sequentially extracted with five solvents based on polarity and residue was subjected to acidic extraction. The filtrates were precipitated for alginates, and resultant supernatant was precipitated for fucoidan. The precipitate was centrifuged; pellet dialyzed and lyophilized to yield crude fucoidan, which was purified by diethylaminoethyl cellulose chromatography and characterized by biochemical tests and Fourier-transform infrared (FT-IR) spectrometry. Solvent extracts and fucoidans were subjected to 2,2-diphenyl-1-picrylhydrazyl assay. Fucoidans were subjected to trypan blue cytotoxicity assay. Results: Antioxidant activity was highest in methanol extracts and Padina crude fucoidan, while lowest in hexane extracts and purified Sargassum fucoidan. Sargassum yielded the highest amount of fucoidan (7.14%). Total carbohydrates increased as Sargassum> Padina > Turbinaria, sulfates as Padina > Turbinaria > Sargassum, and protein content was 0.16±0.001%. Cytotoxicity increased in a dose-dependent manner; the highest and lowest for Padina at 200 mg mL-1 (40%) and 10 mg mL-1 (4%), respectively. Antioxidant and cytotoxic properties exhibited a positive correlation with sulfate content. FT-IR spectral values were characteristic to fucoidan. Conclusion: Fucoidans from the three algae effectively scavenged free radicals and showed good cytotoxic activity. There was a positive correlation between sulfate content and bioactivity of fucoidans, supporting its structure-function relationship. Thus, extracts and fucoidans from these algae are found to be potential candidates for pharmacological applications.